Transfer and Metabolism of the Xenoestrogen Zearalenone in Human Perfused Placenta - Warth, Benedikt (Environ Health Perspect, 2019)
BACKGROUND: Pregnancy is a sensitive condition during which adverse environmental exposures should be monitored thoroughly and minimized whenever possible. In particular, the hormone balance during gestation is delicate, and disturbance may cause acute or chronic long-term health effects. A potential endocrine disruption may be provoked by in utero exposure to xenoestrogens mimicking endogenous estrogens. The mycoestrogen zearalenone (ZEN), a toxic fungal secondary metabolite and mycotoxin found frequently in food and feed, constitutes a prominent example. OBJECTIVES: We performed a comprehensive assessment of the transfer as well as phase I and phase II metabolism of ZEN at the human placental barrier. METHODS: Human placentas were perfused with [Formula: see text] ([Formula: see text]) ZEN for 6 h. Samples from the maternal and fetal compartment, placental tissue, and fetal plasma were analyzed by a highly sensitive UHPLC-MS/MS assay to detect ZEN as well as nine key metabolites ([Formula: see text] , [Formula: see text] , zearalanone, [Formula: see text] , [Formula: see text] , ZEN-14-glucuronide, [Formula: see text] , [Formula: see text] , ZEN-14-sulfate). RESULTS: The model revealed a fast maternofetal transfer of ZEN across the human placental barrier. We also unraveled phase I and phase II metabolism of the parent toxin ZEN into the approximately 70-times more estrogenic [Formula: see text] and the less active ZEN-14-sulfate conjugate, which are effectively released into the maternal and fetal circulation in considerable amounts. CONCLUSIONS: Our findings suggest that exposure to ZEN (such as through consumption of ZEN-contaminated cereal-based products) during pregnancy may result in in utero exposure of the fetus, not only to ZEN but also some of its highly estrogenically active metabolites. In the light of the known affinity of ZEN and potentially co-occurring xenoestrogens to the estrogen receptor, and our results demonstrating placental transfer of ZEN and its metabolites in an ex vivo model, we recommend further research and more comprehensive assessment of gestational exposures in women. https://doi.org/10.1289/EHP4860